Precipitation in Fe-Cu and Fe-Cu-Mn model alloys under irradiation: Dose rate effects. (15th September 2018) - Shu, Shipeng; Almirall, Nathan; Wells, Peter B.; Yamamoto, Takuya; Odette, G. Robert; Morgan, Dane D.
Abstract: Irradiation effects are studied using accelerated-damage experiments in test reactors and charged-particle accelerator facilities. Neutrons and ions create vacancy and self-interstitial defects, in dose unit of displacements per atom (dpa). It is important to understand the effects of irradiation dose rate on microstructural evolution processes, including irradiation enhanced precipitation, to properly interpret results from experiments using accelerated-damage experiments. Here we report on precipitation in Fe-Cu and Fe-Cu-Mn model alloys irradiated at dose rates ranging from ∼10 −10 dpa/s (neutrons) to ∼10 −5 dpa/s (70 MeV Fe ions). Atom probe tomography, small angle neutron scattering, and rate theory models show that precipitation is affected by both dose rate and alloy composition. Higher dose rates: 1) decrease the efficiency of radiation enhanced diffusion, due to increased vacancy-self interstitial recombination; and, 2) increase the rate of ballistic mixing that partly dissolves the precipitate constituents. The key parameter is the rate of ballistic mixing relative to the rate that solutes are reacquired by diffusion. The Mn in the ternary alloy traps vacancies and enhances recombination, leading to very different precipitate evolution kinetics. Graphical abstract: Image 1